2004
DOI: 10.1002/ajh.20164
|View full text |Cite
|
Sign up to set email alerts
|

Essential thrombocythemia terminating in pure erythroleukemia

Abstract: Transformation into acute leukemia is a rare event in essential thrombocythemia (ET). The blasts are usually of myeloid, rarely of megakaryoblastic differentiation. We present the case of a patient with pure erythroleukemia after a nearly 10-year course of ET, which was treated with hydroxyurea. The patient, a 58-year-old male, presented with an elevated thrombocyte count (926,000/mL) and normal values of hemoglobin and leukocytes. After 10 years of therapy with hydroxyurea, the patient developed acute leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…Like Thiele et al [22]we found only one ET patient developing MF in our cohort. However, since this event was associated with a leukaemic transformation and the patient was the only one with MF in the group of ET patients, the fibre increase may not be a feature of ET but rather induced by the blasts [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Like Thiele et al [22]we found only one ET patient developing MF in our cohort. However, since this event was associated with a leukaemic transformation and the patient was the only one with MF in the group of ET patients, the fibre increase may not be a feature of ET but rather induced by the blasts [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Transformation of ET to leukemia demonstrates the pluripotent potential of the neoplastic hemopoietic stem cell, with the ability to transform to leukemia not only of the myeloid but also lymphoid lineage [20]. In this case report, we demonstrate a case of transformation to acute biphenotypic leukemia (BAL).…”
Section: Discussionmentioning
confidence: 85%
“…BAL is believed to arise from a multipotent progenitor cell and carries a poor prognosis. The cytogenetic abnormality of del (20) and the need to use multiple agents to control thrombocytosis in our patient reflect a more aggressive disease. Hence, it is not surprising to see transformation to BAL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we had reported another case of ET with subsequent progression to AE [5], which retrospectively turned out to harbor the wild type of JAK2 in the chronic phase of the disease at diagnosis as well as in AE.…”
Section: Case Reportmentioning
confidence: 99%